Development of A Water-Recycling Pico Hydropower System - Nuhu MOHAMMED; Garkuwa Y. ADAMU; Abubakar A. FACHWAY; Aminu MOHAMMED; Afolayan A. OLASUNKANMI; Odoh F. CHIMEZIE; Muhammad A. YUSUF (FUDMA Journal of Engineering and Technology, 2025)
This paper presents a groundbreaking Pico water-recycling hydropower system designed to transform the kinetic energy of water into clean, affordable electricity. Unlike conventional hydropower systems, the innovative closed-loop design continuously recycles water, making it an ideal solution for areas with limited water resources while maintaining a minimal environmental impact. The system was designed and constructed to have 10 buckets, a net head of 2 m, and a flow rate of 0.0041 0.000124 m3/s, and a return flow rate of 0.000124 m3/s. The turbine achieves an impressive 80% efficiency, thereby generating 24 W of usable electrical output. The results demonstrate that this technology is technically viable, offering an alternative to diesel generators and solar panels in remote settings. The system’s zero-emission production while conserving water through continuous recycling can provide a significant environmental benefit and can contribute to achieving multiple sustainable development goals simultaneously.
Keywords: Pico hydropower, water recycling, Pelton turbine, off-grid energy, sustainable electrification, renewable energy, kinetic energy.